2008
DOI: 10.1021/es071361i
|View full text |Cite
|
Sign up to set email alerts
|

Energy Balance and Emissions Associated with Biochar Sequestration and Pyrolysis Bioenergy Production

Abstract: The implications for greenhouse gas emissions of optimizing a slow pyrolysis-based bioenergy system for biochar and energy production rather than solely for energy production were assessed. Scenarios for feedstock production were examined using a life-cycle approach. We considered both purpose grown bioenergy crops (BEC) and the use of crop wastes (CW) as feedstocks. The BEC scenarios involved a change from growing winter wheat to purpose grown miscanthus, switchgrass, and corn as bioenergy crops. The CW scena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
266
0
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 496 publications
(283 citation statements)
references
References 23 publications
9
266
0
8
Order By: Relevance
“…All show the potential of biochar to improve resource efficiency. Focusing on the value of CO2 reductions, Gaunt and Lehmann [56] determined that biochar application to agricultural land would provide greater GHG emission reductions than using the char for electricity generation, assuming (1) a fertilizer reduction of 10%, which would result in a reduction in N2O emissions of 50% compared to a case without any treatment and (2) the effect of biochar would remain for 10 years after application. If the cost of CO2 emissions is also considered not only the environmental balance but also the economic balance will become considerably attractive in favor of biochar co-production [57].…”
Section: Environmental and Economic Aspects Of Biochar Production Andmentioning
confidence: 99%
“…All show the potential of biochar to improve resource efficiency. Focusing on the value of CO2 reductions, Gaunt and Lehmann [56] determined that biochar application to agricultural land would provide greater GHG emission reductions than using the char for electricity generation, assuming (1) a fertilizer reduction of 10%, which would result in a reduction in N2O emissions of 50% compared to a case without any treatment and (2) the effect of biochar would remain for 10 years after application. If the cost of CO2 emissions is also considered not only the environmental balance but also the economic balance will become considerably attractive in favor of biochar co-production [57].…”
Section: Environmental and Economic Aspects Of Biochar Production Andmentioning
confidence: 99%
“…The increased research and development on strategies to improve and produce bioenergy from renewable energy sources to contribute to the energy needs of developing and developed societies will contribute to the deposition of biochar-like products into the environment [72]. Additionally, it may be produced as a result of uncontrolled bush burning or wild fires and then deposited onto soil [73], and it has been reported that biochar-amended soils have the ability to retain moisture, increase cation exchange capacity (CEC), increase adsorptive capacity and increase pH [74].…”
Section: Current Uses Of Biocharmentioning
confidence: 99%
“…Generally, activated charcoal is alkaline, but may have a pH of 4 to 12 depending on the conditions surrounding the manufacturing process [10] [11]. Its use in cropping systems contributes to the reduction of greenhouse gas emissions [12]. The incorporation of activated charcoal on the soil modifies its water state and influences the root development of plants as well as the fauna of the soil [13].…”
Section: Introductionmentioning
confidence: 99%